Pemberlakuan Sanksi Terhadap Pengabaian Pengelolaan Limbah B3 Medis Di Indonesia - Ayu Putriyana; Shabrina Nasution (UNIB Press, 2025)
The medical hazardous waste management has been regulated in Indonesian laws, but awareness of its management is still at the lowest level. This can be seen from the open dumping of The Medical waste, processing without a permit, waste burning processes that do not comply with quality standards, lack of processing services, storage of hazardous waste that is not stored in its area, storage areas that do not comply with standards, and termination of the use of incinerators because they do not have a permit. This research analyzes the sanctions for neglect of The Medical (Hazardous) waste management provisions. This research is normative juridical research using a descriptive qualitative approach. The research shows that (1) in the laws governing the management of medical hazardous waste, there are provisions for sanctions related to not managing medical hazardous waste properly which are given in stages starting from written warnings, government coercion, administrative fines, freezing of business licenses, revocation business licensing up to criminal sanctions as an ultimum remidium. In addition, (2) it is undeniable that there are several challenges that are quite complex in the management of medical hazardous waste until the management has not run optimally.